Heavy Study Investment in Indonesian College Students: Do Studyholism and Study Engagement Predict Academic Resilience? - M. Fadli Nugraha; Yura Loscalzo (SAGE Open)
Studyholism (SH) is a new potential clinical condition introduced in 2017 by Loscalzo and Giannini to refer to problematic overstudying, specifying that it might be associated with either high or low Study Engagement (SE). We aimed to analyze SH and SE’s predictive role on academic resilience. We gathered 609 Indonesian youths, and we performed a path analysis model. Among the main findings, SH predicts a lack of academic resilience, while SE predicts higher academic resilience. However, SH and SE do not predict time spent studying, and GPA is negatively (although weakly) predicted by SH only. Hence, we provided support for the critical role of SH and SE in predicting students’ academic success and for implementing preventive and clinical interventions to reduce SH and foster SE, given their impact on academic resilience, which, in turn, influences students’ well-being and academic success. Finally, we recommend future research on Studyholism in non-Western countries.